(untitled) (Journal of Hama University, 2021)
The experiment was conducted to study the effect of using different proportions of dried cultured barley in broiler feed mixtures on some productive indicators . Birds were divided into 4 groups and each one included 28 birds and all groups were similar in term of heating ventilation, and all other management treatments except for feeding methods which were related to research plan. Groups of birds were fed by traditional feed mixtures . The control group (G1) was fed by a commercial feed while the other groups were treated by adding a dry cultivated barley to its feed mixtures by 10 % , 15%, and 20% to the groups G2, G3 and G4, respectively Birds were slaughtered at 6 weeks old. Results indicated that there were significant differences (P<0,01) in relation to body weight in the experimental groups comparing with control one at 6 weeks old . This result indicates that adding Cultivated Barley affect body weight whatever the percentage of adding green barley used in the experiment. Results also indicated that cultured barley can replace yellow corn without affecting the characteristics of the carcass, as no significant differences (P≥0,05) were found between experimental and control group for sniping weight, heart, liver, pectorals minor and pectorals major . This is a clear indication that germination improves the nutritional value of barley .